2021 ISHNE/HRS/EHRA/APHRS collaborative statement on mHealth in Arrhythmia Management: Digital Medical Tools for Heart Rhythm Professionals: From the International Society for Holter and Noninvasive Electrocardiology/Heart Rhythm Society/European Heart Rhythm Association/Asia Pacific Heart Rhythm Society. Issue 2 (29th January 2021) - Varma, Niraj; Cygankiewicz, Iwona; Turakhia, Mintu; Heidbuchel, Hein; Hu, Yufeng; Chen, Lin Yee; Couderc, Jean‐Philippe; Cronin, Edmond M.; Estep, Jerry D.; Grieten, Lars; Lane, Deirdre A.; Mehra, Reena; et al.
Abstract: This collaborative statement from the International Society for Holter and Noninvasive Electrocardiology/Heart Rhythm Society/European Heart Rhythm Association/Asia Pacific Heart Rhythm Society describes the current status of mobile health ("mHealth") technologies in arrhythmia management. The range of digital medical tools and heart rhythm disorders that they may be applied to and clinical decisions that may be enabled are discussed. The facilitation of comorbidity and lifestyle management (increasingly recognized to play a role in heart rhythm disorders) and patient self‐management are novel aspects of mHealth. The promises of predictive analytics but also operational challenges in embedding mHealth into routine clinical care are explored. Abstract :